Anomalous dielectric relaxation peak in Nb-doped SrTiO3 single crystals. Issue 17 (1st September 2022) - He, Zichen; Cao, Minghe; Furman, Eugene; Lanagan, Michael T.; Yuan, Mengxue; Meng, Xiangyu; Wu, Jinsong; Hao, Hua; Yao, Zhonghua; Yu, Zhiyong; Liu, Hanxing
Abstract: Anomalous dielectric relaxation appears in Nb-doped SrTiO3 (SNT) single crystal with relaxation rate displaying unusual slowing down with increasing temperature. Dielectric measurements show that the resistivity increases with temperature. Raman spectrum and the spherical aberration-corrected transmission electron microscope (STEM) show the existence of polar nano regions (PNRs) in the crystal. The temperature-dependence of DC conductivity and current-voltage (I–V) curves suggest that this anomalous behavior happens at the interfaces of PNRs. The evolution of the anomalous relaxation peak in the annealed samples indicates that this effect is simultaneously affected by the carrier concentration and the interface structure. The anomalous dielectric relaxation is reminiscent of the positive temperature coefficient of resistance (PTCR) effect in a polycrystalline material. The resistive switching effect makes such materials to have potential application value in switches, sensors, and device miniaturization.